STAT3 signaling modulates the immune response induced after antigen targeting to conventional type 1 dendritic cells through the DEC205 receptor - Sulczewski, Fernando Bandeira; Martino, Larissa Alves; Salles, Davi; Yamamoto, Márcio Massao; Rosa, Daniela Santoro; Boscardin, Silvia Beatriz (Frontiers in Immunology, 2022)
Conventional dendritic cells (cDC) are a group of antigen-presenting cells specialized in priming T cell responses. In mice, splenic cDC are divided into conventional type 1 DC (cDC1) and conventional type 2 (cDC2). cDC1 are specialized to prime the Th1 CD4+T cell response, while cDC2 are mainly associated with the induction of follicular helper T cell responses to support germinal center formation. However, the mechanisms that control the functions of cDC1 and cDC2 are not fully understood, especially the signaling pathways that can modulate their ability to promote different CD4+ T cell responses. Here, we targeted a model antigen for cDC1 and cDC2, through DEC205 and DCIR2 receptors, respectively, to study the role of the STAT3 signaling pathway in the ability of these cells to prime CD4+ T cells. Our results show that, in the absence of the STAT3 signaling pathway, antigen targeting to cDC2 induced similar frequencies of Tfh cells between STAT3-deficient mice compared to fully competent mice. On the other hand, Th1 and Th1-like Tfh cell responses were significantly reduced in STAT3-deficient mice after antigen targeting to cDC1 via the DEC205 receptor. In summary, our results indicate that STAT3 signaling does not control the ability of cDC2 to promote Tfh cell responses after antigen targeting via the DCIR2 receptor, but modulates the function of cDC1 to promote Th1 and Th1-like Tfh T cell response after antigen targeting via the DEC205 receptor.